The rebirth of the Middle East - Rosenberg, Jerry Martin (Hamilton Books, 2009)
In The Rebirth of the Middle East,Rosenberg discusses how peace, stability, and prosperity are dependent upon economic and trade relations between Israel and Palestine, as well as other neighboring Arab and Muslim countries. The world is poised to participate in this healing process with funding and training and lacks only the needed conditions to proceed. Rosenberg asserts that this process of stabilization can benefit from a reinvented Marshall Plan, modeled on the 1948 U.S. humanitarian European Recovery Program. In the long run, success will be measured by the creation of a Middle East Economic Community.